Factors that influence in the turnout in ballet dancers with knee pain - Paula Fiquetti Silveira; Sérgio Rocha Piedade (Universidade de São Paulo, 2014)
The turnout, primary gesture in classical ballet, refers the 180º of the feet. The lateral rotation provides the greatest amount of degrees necessary to perform the position perfectly. If performed improperly, it can generate problems, specialy in the knees, causing pain. The aim of this study was to evaluate the factors that influence the implementation of turnout in adolescents ballet dancers with knee pain and to compare them to the dancers without pain. Twenty three (23) ballet dancers with knee pain and 26 ballet dancers without pain were evaluated for range of motion of external rotation of the hip, muscle strength, femoral neck anteversion and static and dynamic turnout. The angles were measured with a manual goniometer, and the strength of the abductor muscle groups, external rotators and hip extensors with isometric dynamometer. The analysis was performed using ANOVA and Mann-Whitney. Range of motion of external rotation of the hip, femoral neck anteversion and muscle strength were similar between groups. The dynamic turnout was lower in ballet dancers with knee pain (p=0.02) and ballerinas with angular deficits above 10% over the static group had lower turnout under the bilateral extensor muscle group (p=0.04 and 0.03, right left) and right abductor (p=0.03). Although anatomical factors can influence the lateral rotation of the turnout, the angle decreased dynamic turnout was related to the group of dancers with pain. This suggests that training based on proximal awareness of movement can prevent and minimize burdens on the knees of classical dancers teens.